2023
DOI: 10.1002/jssc.202201061
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ivacaftor by liquid chromatography techniques in pharmaceutical formulation with interlaboratory comparison and characterization of five novel degradation products by high‐performance liquid chromatography ion trap time‐of‐flight mass spectrometry

Abstract: Cystic fibrosis is a life‐threatening genetic disease that causes damage to the lungs. Ivacaftor, the first drug to target the underlying defect of the disease caused by specific mutations, improves outcomes and reduces hospitalizations. In this study, quantitative determination of ivacaftor was performed by liquid chromatography, while high‐resolution mass spectrometric analyses were performed for qualitative determination. The validation studies of the developed methods were performed according to Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In fact, in previous methods developed for IVA or LUMA analysis (one of the authors also contributed), stability studies have shown that the active ingredients are quite stable [20,21]. However, in this study, stability studies were carried out meticulously because IVA and LUMA were mixed in the working solutions and ava contributed as IS.…”
Section: Resultsmentioning
confidence: 95%
“…In fact, in previous methods developed for IVA or LUMA analysis (one of the authors also contributed), stability studies have shown that the active ingredients are quite stable [20,21]. However, in this study, stability studies were carried out meticulously because IVA and LUMA were mixed in the working solutions and ava contributed as IS.…”
Section: Resultsmentioning
confidence: 95%
“…Another important point is that SIM is specific or selective. It is the determination of active pharmaceutical ingredient (API) in the presence of excipients, additives, and degradation products that are expected to be present in the specific SIM [9,10]. Selective SIM is the technique that measures API and all degradation products in the presence of excipients and additives [9,11,12].…”
Section: Introductionmentioning
confidence: 99%